Predicting entrepreneur’s income status using logistic regression: a case study of GIATMARA incubator program / Sharifah Nurnajwa Syed Mashor - Syed Mashor, Sharifah Nurnajwa (2013)
The entrepreneur is commonly seen as a business leader and innovator of new ideas and business processes. Entrepreneurship education is found to contribute significantly to risk-taking, the formation of new ventures, and the propensity to be self-employed. MARA has developed a program named Incubator GIATMARA Program. The program is to give an early exposure about entrepreneurship and help GIATMARA’s students become successful entrepreneurs. The research used simple random sampling and questionnaire to collect respondents. From the findings, this study found that the best method to be applied in logistic regression is enter method. Factors that influence entrepreneur’s income are number of worker that the entrepreneurs have and capital sources other than MARA.